Interactional injustice and interpersonal deviance in a workplace / Khairul Azfar Adzahar ... [et al.] - Adzahar, Khairul Azfar; Mohd Hussain, Siti Hajar; Saharan, Mohd Shafiz; Mohamad, Masilah (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2020)
When the employees feel that they were treated inequitably, no respect and concern by the employer, they tend to retaliate, and it is a common cause of workplace sabotage (Shim, 2008). A good manager will effectively exercise open, consistent, fair, and direct interaction with employees. According to Burton et al., (2005), interactional injustice occurs when the enactment of formal procedures or the explanation of such processes to employees was conducted unfairly to each different employee. Violation of interactional justice in a workplace happens in leader-member relationships when they promote or treat an employee not based on merit and performance but merely social connections and ties (Gonthier, 2002). Abusive supervision from the leader created all sorts of employee deviance which influenced the willingness of the employees to show negative behaviours (Mitchell & Ambrose, 2007). Unfortunately, many among us had faced such interactional injustice in the workplace. Some are due to the fact of different racial status, religions, and sexual orientations. What is being more concerned is that even the slightest diversity could lead to problems in workplace such as being born in a certain race, having different skin tone and just because one prefers to speak in another language than the rest. Based on Gillligan’s (1996), employees with lower positions in an organisation have a higher possibility of having deviant acts. Not limited to that, negative relationships also happened in member-organisations relationships (Gonthier, 2002). Supported by (Mitchell & Ambrose, 2007), abusive supervision will influence the retaliation from both, supervisor directed deviance and displaced deviant behaviours which targeted other co-workers.